Feeding behaviour of intermittently-fed broilers and the effects of crop retention time and NSPase on digesta dynamics of barley diets - M. Ahmad; L.S. Bassi; J. Apajalahti; S.K. Sjurseth; A. Smith; B. Svihus (Animal Feed Science and Technology, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Use of statistical models to determine the optimal concentration of metabolizable energy for growth performance of broiler chickens - F.O. Marx; M.V.N. Alvarez; L.S. Bassi; A.P. Félix; E.L. Krabbe; S.G. Oliveira; A. Maiorka (Livestock Science, 2023)

A multi-reference parent nested-association mapping population to dissect the genetics of quantitative traits in durum wheat - Samir Alahmad; Yichen Kang; Eric Dinglasan; Dilani Jambuthenne; Hannah Robinson; Yongfu Tao; Jason A. Able; Jack Christopher; Kai P. Voss-Fels; Filippo M. Bassi; Lee T. Hickey (Genetic Resources and Crop Evolution, 2023)

From COVID-19 to Green Recovery with natural capital accounting - Michael Vardon; Paul Lucas; Steve Bass; Matthew Agarwala; Andrea M. Bassi; Diane Coyle; Anthony Dvarskas; Catherine A. Farrell; Oliver Greenfield; Steven King; Martin Lok; Carl Obst; et al. (Ambio, 2023)
The COVID-19 pandemic and related social and economic emergencies induced massive public spending and increased global debt. Economic recovery is now an opportunity to rebuild natural capital alongside financial, physical, social and human capital, for long-term societal benefit. Yet, current decision-making is dominated by economic imperatives and information systems that do not consider society’s dependence on natural capital and the ecosystem services it provides. New international standards for natural capital accounting (NCA) are now available to integrate environmental information into government decision-making. By revealing the effects of policies that influence natural capital, NCA supports identification, implementation and monitoring of Green Recovery pathways, including where environment and economy are most positively interlinked.

Institutional and farm-level challenges limiting the diffusion of new varieties from public and CGIAR centers: The case of wheat in Morocco - Yigezu A. Yigezu; Zewdie Bishaw; Abdoul Aziz Niane; Jeffrey Alwang; Tamer El-Shater; Mohamed Boughlala; Aden Aw-Hassan; Wuletaw Tadesse; Filippo M. Bassi; Ahmed Amri; Michael Baum (Food Security, 2021)
Low adoption of agricultural technologies slows efforts to increase agricultural productivity and enhance rural livelihoods in developing countries. A large body of literature has sought explanations for the problem, but the focus has been mainly on micro-level farm and community factors affecting adoption. Institutional factors such as policies and market conditions, which are also important, have been largely overlooked and, few, if any, studies combine the two levels of analysis. We use Morocco as a case study to analyze institutional and farm-level factors affecting diffusion and adoption of improved wheat varieties. Results show both sides to be important. Institutional factors such as overly stringent variety testing procedures, imbalance of power among actors in the seed sector and ill-conceived variety licensing contracts limit access to seeds of more recently released varieties. Adoption of older new varieties is found to be affected by farm and farmer characteristics, but imperfect access to new seeds, sometimes associated with the failings identified above, is also a constraint. Findings signal the need for increased private engagement in seed multiplication; revised variety testing procedures; alternative royalty mechanisms; and enhanced linkages between public research and private seed companies.

Modulation of hypercapnic respiratory response by cholinergic transmission in the commissural nucleus of the solitary tract - Werner I. Furuya; Mirian Bassi; José V. Menani; Eduardo Colombari; Daniel B. Zoccal; Débora S. A. Colombari (Pflügers Archiv - European Journal of Physiology, 2020)

Postmortem analysis of WWI human remains from Italian glaciers in rare environmental conditions - Daniel Gaudio; L. De Luca; V. Cirielli; M. Caccianiga; C. Bassi; N. Cappellozza; A. Galassi; F. Nicolis; C. Cattaneo (Archaeological and Anthropological Sciences, 2019)

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Behaviour of repetitive non-coding DNA in response to heavy metal stress in the protonemata of Funaria hygrometrica - P. Bassi; A. Basile; S. Sorbo (Plant Biosystems, 2015)

The olfactory function is impaired in patients with idiopathic inflammatory myopathies - L. Iaccarino; N. Shoenfeld; M. Rampudda; M. Zen; M. Gatto; A. Ghirardello; N. Bassi; L. Punzi; Y. Shoenfeld; A. Doria (Immunologic Research, 2014)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

Radiation hybrid QTL mapping of Tdes2 involved in the first meiotic division of wheat - F. M. Bassi; A. Kumar; Q. Zhang; E. Paux; E. Huttner; A. Kilian; R. Dizon; C. Feuillet; S. S. Xu; S. F. Kianian (Theoretical and Applied Genetics, 2013)

Central leptin replacement enhances chemorespiratory responses in leptin-deficient mice independent of changes in body weight - Mirian Bassi; Humberto Giusti; Cristiane Mota Leite; Janete A. Anselmo-Franci; Jussara M. do Carmo; Alexandre A. da Silva; John E. Hall; Eduardo Colombari; Mogens L. Glass (Pflügers Archiv - European Journal of Physiology, 2012)

Comparative transcript profiling of apricot (Prunus armeniaca L.) fruit development and on-tree ripening - George A. Manganaris; Angela Rasori; Daniele Bassi; Filippo Geuna; Angelo Ramina; Pietro Tonutti; Claudio Bonghi (Tree Genetics & Genomes, 2011)

Improvement of biomolecular methods for the identification and typing of Escherichia coli O157:H7 isolated from raw meat - A. Paris; S. Bonardi; C. Bacci; E. Boni; F. Salmi; L. Bassi; F. Brindani (Veterinary Research Communications, 2010)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Parallel pigment and transcriptomic analysis of four barley Albina and Xantha mutants reveals the complex network of the chloroplast-dependent metabolism - Chiara Campoli; Stefano Caffarri; Jan T. Svensson; Roberto Bassi; A. Michele Stanca; Luigi Cattivelli; Cristina Crosatti (Plant Molecular Biology, 2009)

Occurrence of TRGV-BJ hybrid gene in SV40-transformed fibroblast cell lines - L. P. G. D’Arce; C. L. Bassi; A. L. Fachin; G. A. S. Passos; E. T. Sakamoto-Hojo (Genetica, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

Formate binding near the redox-active TyrosineD in Photosystem II: consequences on the properties of TyrD - Rainer Hienerwadel; Samuel Gourion-Arsiquaud; Matteo Ballottari; Roberto Bassi; Bruce A. Diner; Catherine Berthomieu (Photosynthesis Research, 2005)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Suborganellar localisation and effect of light on Helianthus tuberosus chloroplast transglutaminases and their substrates - L. Dondini; S. Del Duca; L. Dall'Agata; R. Bassi; M. Gastaldelli; M. Della Mea; A. Di Sandro; I. Claparols; D. Serafini-Fracassini (Planta, 2003)

The structure of duplications on human acrocentric chromosome short arms derived by the analysis of 15p - I. Piccini; L. Ballarati; C. Bassi; M. Rocchi; A. Marozzi; E. Ginelli; R. Meneveri (Human Genetics, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Generalized cross-covariances and their estimation - H. R. Künsch; A. Papritz; F. Bassi (Mathematical Geosciences, 1997)